2016
DOI: 10.1093/mnras/stw2082
|View full text |Cite
|
Sign up to set email alerts
|

SKA weak lensing – I. Cosmological forecasts and the power of radio-optical cross-correlations

Abstract: We construct forecasts for cosmological parameter constraints from weak gravitational lensing surveys involving the Square Kilometre Array (SKA). Considering matter content, dark energy and modified gravity parameters, we show that the first phase of the SKA (SKA1) can be competitive with other Stage III experiments such as the Dark Energy Survey (DES) and that the full SKA (SKA2) can potentially form tighter constraints than Stage IV optical weak lensing experiments, such as those that will be conducted with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 88 publications
2
82
0
Order By: Relevance
“…For this analysis, we first assume that one is not sharing data between the two surveys, but only use the final catalogs so that photo-z accuracy is the standard for each survey taken on its own. The data vector is then Harrison et al (2016), to which we refer the reader for further details. For a given ℓ, we the define the S/N as  =…”
Section: Weak-lensing S/n and Photo-z Accuracy: An Examplementioning
confidence: 99%
“…For this analysis, we first assume that one is not sharing data between the two surveys, but only use the final catalogs so that photo-z accuracy is the standard for each survey taken on its own. The data vector is then Harrison et al (2016), to which we refer the reader for further details. For a given ℓ, we the define the S/N as  =…”
Section: Weak-lensing S/n and Photo-z Accuracy: An Examplementioning
confidence: 99%
“…Previously, in Harrison et al (2016) (hereafter, Paper I), we have constructed forecasts for cosmological parameter estimation. We have shown that the first phase of the SKA (SKA1) can be competitive with experiments such as the Dark Energy Survey (DES), and that the full SKA (SKA2) can potentially provide us with tighter constraints from weak lensing alone than optical cosmic shear surveys such as the Large Synoptic Survey Telescope (LSST) or the European Space Agency Euclid satellite.…”
Section: Introductionmentioning
confidence: 99%
“…The idea, suggested by Blain (2002) and Morales (2006), is to measure the departure from perpendicularity of the rotation axis of a disk galaxy to the major axis of the galaxy disk image and use this measure as an estimate of the shear field at the galaxy's position (see also Huff et al 2013). Finally, by cross-correlating the shear estimators of optical and radio surveys, uncorrelated systematic errors may be mitigated (Patel et al 2010;Demetroullas & Brown 2016;Harrison et al 2016;Camera et al 2016). For a general overview of radio weak lensing see Brown et al (2015).…”
Section: Introductionmentioning
confidence: 99%